2015
DOI: 10.1242/dev.130534
|View full text |Cite
|
Sign up to set email alerts
|

Single epicardial cell transcriptome sequencing identifies Caveolin-1 as an essential factor in zebrafish heart regeneration

Abstract: In contrast to mammals, adult zebrafish have a high capacity to regenerate damaged or lost myocardium through proliferation of cardiomyocytes spared from damage. The epicardial sheet covering the heart is activated by injury and aids muscle regeneration through paracrine effects and as a multipotent cell source, and has received recent attention as a target in cardiac repair strategies. Although it is recognized that epicardium is required for muscle regeneration and itself has high regenerative potential, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(129 citation statements)
references
References 64 publications
(82 reference statements)
4
125
0
Order By: Relevance
“…Furthermore, one of Tcf21’s functions is to suppress the smooth muscle gene Smα in the fibroblast lineage, and the ectopic expression of Smα in Tcf21 mutants is seen in epicardial cells at the surface (63). A lineage decision within the epicardium is supported by inducible lineage labeling using Wt1-CreER , which shows that most smooth muscle cells are derived from the early epicardium (60, 64), which is consistent with the epicardium itself being a heterogeneous population (43, 65). Further experiments are required to confirm whether the initiation of EMT is part of the differentiation program.…”
Section: Coronary Vessel Progenitor Cells and Their Differentiation Pmentioning
confidence: 63%
“…Furthermore, one of Tcf21’s functions is to suppress the smooth muscle gene Smα in the fibroblast lineage, and the ectopic expression of Smα in Tcf21 mutants is seen in epicardial cells at the surface (63). A lineage decision within the epicardium is supported by inducible lineage labeling using Wt1-CreER , which shows that most smooth muscle cells are derived from the early epicardium (60, 64), which is consistent with the epicardium itself being a heterogeneous population (43, 65). Further experiments are required to confirm whether the initiation of EMT is part of the differentiation program.…”
Section: Coronary Vessel Progenitor Cells and Their Differentiation Pmentioning
confidence: 63%
“…Interestingly, in migrating PGCs, Cav1-GFP is primarily localized to structures in the vicinity of the plasma membrane at the back of the migrating cells, sub-cellular localization that appeared inconsistent with a role in bleb formation (Figure S3B). Nevertheless, we proceeded to examine PGC behavior in mutant embryos lacking the maternal and zygotic of both Cav1 and Cav3 proteins, mutants in which caveolae formation and function are severely impaired, such that they are strongly reduced in number (Cao et al, 2016; Garcia et al, 2017). In these experiments, despite the lack of both caveolin proteins, we observed no effect on either bleb expansion or on the ability of the cells to actively migrate and reach their target (Figure S3C, Movie S2).…”
Section: Resultsmentioning
confidence: 99%
“…cav1;cav3 mutants fish were previously described (Cao et al, 2016; Garcia et al, 2017). Briefly, the cav1 1104 mutants were generated using TALEN pairs to target to the common sequence of both cav1 isoforms, leading to a 23nt deletion and the cav3 pd1149 mutant allele was generated using two CRISPRs that remove a 765-bp region between exon 1 and intron 1, resulting in the deletion of 90 bp of coding sequence.…”
Section: Star Methodsmentioning
confidence: 99%
“…Given that a recent study of single cell transcriptome analysis of epicardial cells demonstrated heterogenity of epicardial cells (Cao et al, 2015), it is possible that distinct populations of epicardial cells differentially respond to injury-induced stimuli, and migrate to cover the myocardium or migrate into the myocardium to support vasculogenesis. Further molecular studies will be needed to understand how distinct populations of epicardial cells migrate during heart regeneration.…”
Section: Cell Migration During Zebrafish Heart Regenerationmentioning
confidence: 99%